Experimental Investigation of Tribology-Related Topography Parameters of Hard-Turned and Ground 16MnCr5 Surfaces - Viktor Molnar (Lubricants, 2023)
Several surface topography parameters are available for the quantification of tribological properties of machined surfaces. Although these parameters and their influences are widely studied, there are contradictory findings due to the nature of the topography parameters, i.e., the behavior of different materials and cutting tool interactions lead to relatively varying numerical results. A comprehensive study of these interactions can contribute to more exact industrial machining applications. In this study, tribology-related 3D topography parameters of hard-machined (hard-turned and ground) surfaces were analyzed. The machining experiments were carried out based on a detailed design of the experiment; the analyzed material was case-hardened low-carbon content steel, which is widely used for automotive, industrial components such as bearings or gears. From the topography data, response function, correlation, and relative deviation analyses were carried out for the analyzed topography parameters, and tribology maps were created to support the selection of optimal cutting parameter values.